On the synergistic effect of sulfonic functionalization and acidic adhesive conditioning to enhance the adhesion of PEEK to resin-matrix composites. Issue 4 (April 2021) - Escobar, Mario; Souza, Júlio C.M.; Barra, Guilherme M.O.; Fredel, Márcio C.; Özcan, Mutlu; Henriques, Bruno
Abstract: Objective: The objective of this study was to evaluate the combined effect of the sulfuric acid etching and an acidic adhesive conditioning on the shear bond strength of PEEK to a resin-matrix composite. Materials and methods: Forty PEEK specimens were assigned randomly to 4 groups for H2 SO4 etching followed by universal adhesive (pH at 2.5) conditioning for 0, 1, 3, and 5 min. Thirty PEEK specimens were divided into 3 groups for only acidic adhesive conditioning for 0, 1, 3, and 5 min. After the light-curing of the adhesive, a nanohybrid resin composite was applied onto the surfaces and then light-cured following the manufacturer`s guidelines. All specimens were stored in distilled water at 37 °C for 24 h mechanical testing. Shear bond strength tests were performed using a universal testing machine. Surfaces were analyzed by SEM, light interferometry, FTIR, and liquid contact angle measurement. Statistical analysis was performed by one-way ANOVA and Tukey's post hoc tests ( p < 0.05). Results: No adhesion was achieved between untreated PEEK a resin-matrix composite, regardless of the adhesive conditioning time points. Shear bond strength of H2 SO4 -etched PEEK to resin-matrix composite increased with time (0 mmin. 4.95 ± 2.86 MPa < 1 min: 9.35 ± 2.26 MPa < 3 min: 17.84 ± 2.82 MPa < 5 min: 21.43 ± 5.00 MPa). SEM images revealed a significant modification of PEEK surface topography after the H2 SO4 etching. Significance: The acidic adhesive was unable to modify the untreated PEEK surface to establish an effective adhesion although a synergistic effect was noticed when the universal (acidic) adhesive was applied over a H2 SO4 -etched PEEK surface, thus improving the PEEK to resin-matrix composite adhesion.